2008
DOI: 10.1016/j.prostaglandins.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α negatively regulates bone resorption in murine osteoclast development

Abstract: SUMMARYProstaglandin (PG) E 2 promotes osteoclastic cell differentiation, but the physiological function of PGF 2α remains unclear. We examined the physiological effects of PGF 2α on osteoclast differentiation using a murine cell line, RAW264, and the column-purified murine bone marrow cells, both of which are differentiable into osteoclast-like multi-nuclear cells. Although PGF 2α did not affect the number of differentiated osteoclasts, PGF 2α reduced the bone resorption activity of osteoclasts developed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Considering that osteoclasts enlarge by fusion, and thus resorb bone efficiently (Yagi et al, 2005), they stated that PGF2α inhibits preosteoclast cell fusion or enlargement of osteoclast via a specific receptor (FP) signaling. These observations were in line with the fact that PGF2α did not induce osteoclast apoptosis and did not affect the expression of specific genes of osteoclast differentiation, such as NFATc1, CtpK, and MMP9 (Kamon et al, 2008). It is well documented that during bone remodeling the resorption phase is followed by the reversal phase comprising the differentiation of osteoblast precursors and the discontinuation of bone resorption with osteoclast apoptosis; after osteoblast activation, osteoblasts lay down new bone material until the resorbed bone is entirely replaced by a new one (Hill, 1998; Matsuo and Irie, 2008).…”
Section: Pgf2α Affects Osteoclast Formationsupporting
confidence: 66%
See 1 more Smart Citation
“…Considering that osteoclasts enlarge by fusion, and thus resorb bone efficiently (Yagi et al, 2005), they stated that PGF2α inhibits preosteoclast cell fusion or enlargement of osteoclast via a specific receptor (FP) signaling. These observations were in line with the fact that PGF2α did not induce osteoclast apoptosis and did not affect the expression of specific genes of osteoclast differentiation, such as NFATc1, CtpK, and MMP9 (Kamon et al, 2008). It is well documented that during bone remodeling the resorption phase is followed by the reversal phase comprising the differentiation of osteoblast precursors and the discontinuation of bone resorption with osteoclast apoptosis; after osteoblast activation, osteoblasts lay down new bone material until the resorbed bone is entirely replaced by a new one (Hill, 1998; Matsuo and Irie, 2008).…”
Section: Pgf2α Affects Osteoclast Formationsupporting
confidence: 66%
“…Osteoclast differentiation and survival is controlled by several factors, such as the receptor activator of nuclear factor kB ligand (RANKL), PTH, activated vitamin D3, and PGE2 (Yasuda et al, 1998; Suda et al, 1999). In this context, Kamon et al (2008) have elucidated the effects of PGF2α on osteoclast development; the authors argued that PGF2α suppressed osteoclast‐mediated bone resorption by activating calcitonin‐dependent PKC signaling cascade. Considering that osteoclasts enlarge by fusion, and thus resorb bone efficiently (Yagi et al, 2005), they stated that PGF2α inhibits preosteoclast cell fusion or enlargement of osteoclast via a specific receptor (FP) signaling.…”
Section: Pgf2α Affects Osteoclast Formationmentioning
confidence: 99%
“…Studies on murine osteoclast development suggest that PGF 2␣ would inhibit bone resorption (Kamon et al, 2008). FP receptor expression has been detected in primary human osteoblasts (Sarrazin et al, 2001), and in UMR-106 cells, functional FP receptors were identified (Yamaguchi et al, 1988).…”
Section: Fp Receptorsmentioning
confidence: 99%
“…Differences were considered significant when P < 0.05. Statistical analysis was performed using Excel 2004 (Microsoft, Redmond, WA, USA) with the add-in software Statical (Kamon et al 2008).…”
Section: Discussionmentioning
confidence: 99%